# sqrt(6x-15)=sqrt(4x-3)

## Simple and best practice solution for sqrt(6x-15)=sqrt(4x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for sqrt(6x-15)=sqrt(4x-3) equation:

Simplifying
sqrt(6x + -15) = sqrt(4x + -3)
Reorder the terms:
qrst(-15 + 6x) = sqrt(4x + -3)
(-15 * qrst + 6x * qrst) = sqrt(4x + -3)
(-15qrst + 6qrstx) = sqrt(4x + -3)
Reorder the terms:
-15qrst + 6qrstx = qrst(-3 + 4x)
-15qrst + 6qrstx = (-3 * qrst + 4x * qrst)
-15qrst + 6qrstx = (-3qrst + 4qrstx)
Solving
-15qrst + 6qrstx = -3qrst + 4qrstx
Solving for variable 'q'.
Move all terms containing q to the left, all other terms to the right.
Add '3qrst' to each side of the equation.
-15qrst + 3qrst + 6qrstx = -3qrst + 3qrst + 4qrstx
Combine like terms: -15qrst + 3qrst = -12qrst
-12qrst + 6qrstx = -3qrst + 3qrst + 4qrstx
Combine like terms: -3qrst + 3qrst = 0
-12qrst + 6qrstx = 0 + 4qrstx
-12qrst + 6qrstx = 4qrstx
Add '-4qrstx' to each side of the equation.
-12qrst + 6qrstx + -4qrstx = 4qrstx + -4qrstx
Combine like terms: 6qrstx + -4qrstx = 2qrstx
-12qrst + 2qrstx = 4qrstx + -4qrstx
Combine like terms: 4qrstx + -4qrstx = 0
-12qrst + 2qrstx = 0
Factor out the Greatest Common Factor (GCF), '2qrst'.
2qrst(-6 + x) = 0
Ignore the factor 2.
Subproblem 1Set the factor 'qrst' equal to zero and attempt to solve:
Simplifying
qrst = 0
Solving
qrst = 0
Move all terms containing q to the left, all other terms to the right.
Simplifying
qrst = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-6 + x)' equal to zero and attempt to solve:
Simplifying
-6 + x = 0
Solving
-6 + x = 0
Move all terms containing q to the left, all other terms to the right.
Add '6' to each side of the equation.
-6 + 6 + x = 0 + 6
Combine like terms: -6 + 6 = 0
0 + x = 0 + 6
x = 0 + 6
Combine like terms: 0 + 6 = 6
x = 6
Add '-1x' to each side of the equation.
x + -1x = 6 + -1x
Combine like terms: x + -1x = 0
0 = 6 + -1x
Simplifying
0 = 6 + -1x
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`